Insulinoma About a new case - Perrier, José Pedro; Belloso, Rogelio; Bonifazio, Juan L; Moran, Silvia (Cirugía del Uruguay, 2003)
A case of operated and cured insulinoma leads to a revision of existing literature. One of the main problems líes in attaining diagnostic confirmation which requires discarding other causes far hypoglycernia and multiendocrinal neoplasias. To this should be added the difficult topographic diagnosis. The main reasons is the small size of these tumors and the highly sensitivity of the numerous procedures employed. Palpation together with intraoperative ultrasound scanning is the most cost-effective among them. Surgery, whenever possible, is still sale curative and elective treatment far enucleation. Operative mortality is low, between O and 7.7% but morbility is high, dorninated by pancreatic fistulas which may be found in almost 49% of cases